ANALYSIS OF METEOROLOGICAL DROUGHT PROPAGATION TOWARDS HYDROLOGICAL DROUGHT IN THE UPPER BRANTAS WATERSHED, EAST JAVA - Samba Wirahma; I Putu Santikayasa; Muh Taufik; Findy Renggono (BPPT, 2022)
Abstract Drought is defined as a water deficit condition from normal conditions in the hydrological system. Hydrological drought is a complex process that is preceded by a rainfall deficit. Unlike many other natural disasters, droughts develop slowly, making it difficult to pinpoint the beginning and end of a drought event. Research that focuses on studying the propagation of meteorological drought to hydrological drought is fundamental to revealing the processes and mechanisms of drought propagation. Drought propagation describes the change of meteorological drought signal into hydrological drought through the hydrological cycle. This study aims to analyze the characteristics of drought and evaluate the propagation of drought in the Upper Brantas watershed of East Java. This study uses the Standardized Precipitation Index (SPI) and Standardized Streamflow Index (SSI) methods with an accumulated time of 1, 3, 6, and 12 months to analyze meteorological and hydrological drought characteristics, while the drought propagation was analyzed using Pearson correlation. The results showed that the duration and severity of drought increased with the increase in the period of accumulation of SPI and SSI, while the number of drought events was inversely proportional to the period of accumulation of SPI and SSI. The severity of hydrological drought is higher than the severity of meteorological. The worst hydrological drought (SSI1 = -22.9) with a duration of 12 months occurred in 1997-1998. The high correlation in the condition that there is no time lapse between SSI and SPI shows that the meteorological drought indicator with SPI has the potential to be used as an early detection tool for hydrological drought in the Upper Brantas watershed. This research can be the first step to developing a hydrological drought early detection technique that is very useful in water resource management in watersheds for hydropower operations.